(untitled) (Research, Society and Development, 2020)
In order to evaluate the effect of sodium butyrate on the performance of juvenile tilapia 400 fish (28.55 ± 1.55 g) were used, distributed randomly in 20 tanks (250 L) connected in a closed water circulation system. For 55 days, five levels of sodium butyrate (0, 0.5, 1.0, 1.5 and 2.0 g kg-1) were tested, with each experimental unit represented by 20 fish. To evaluate the treatments, the zootechnical performance, the hepatosomatic index, the viscerosomatic relationship, the centesimal composition of the fish, the hematology and the histology of the intestine were analyzed. Significant differences were observed with quadratic behavior for fish weight gain and specific growth factor, with 1.21 g kg-1 being the best result found for weight gain, while for growth factor 1.13 g kg-1 of organic acid. The feed conversion and the viscerosomatic relationship showed linear behavior, reducing the values ​​in relation to the increase in the level of sodium butyrate. In the hematological analysis, triglyceride levels showed a significant difference for the treatment with 0.5 g kg-1, which was 190.75 mg dl-1. In the histological analysis of the intestines and fish composition, there was no significant difference between treatments. The evaluated data demonstrate an effective action of sodium butyrate with the best result for fish performance at the level of 1.21 g kg-1.